Investigating the Role of Fetal Gene Expression in Preterm Birth. (June 2017) - Vora, Neeta L.; Smeester, Lisa; Boggess, Kim; Fry, Rebecca C.
Second-trimester amniotic fluid supernatant (AFS) contains cell-free fetal RNA (cffRNA) transcripts that can provide information about fetal gene expression. In a retrospective case–control study, we measured second-trimester fetal gene expression using cffRNA extracted from AFS in women who had spontaneous preterm birth (sPTB) <34 weeks and in women who delivered >37 weeks. We extracted cffRNA from AFS of women with singletons who had second-trimester genetic amniocenteses. Twenty-one gravidas who had sPTB and 21 term controls were matched 1:1 for maternal age, fetal sex, race, gestational age (GA) at the time of amniocentesis, and medication exposure. Cell-free fetal RNA was extracted and hybridized to a customized 65-gene NanoString panel containing genes related to oxidative stress, inflammation, and hypothalamic–pituitary–adrenal (HPA) axis and included 15 housekeeping genes. Two models were run, 1 examining sPTB in relation to case/control status and 1 examining sPTB in relation to GA as a continuous variable. Among cases, the gene expression of nitric oxide synthase 1 ( NOS1 ), d -aspartate oxidase ( DDO ), and Beta-2-microglobulin ( B2M ) was higher than controls ( P value < .05; false discovery rate–corrected Q value of ≤0.10). Nitric oxide synthase 1 and DDO are genes associated with oxidative stress; B2M is a marker of the fetal inflammatory response. Fetal HPA gene expression is not associated with GA at delivery or sPTB in second-trimester AFS. Alterations of fetal gene expression related to inflammation and oxidative stress antedate clinical symptoms and may be useful for early identification of patients at risk of having an sPTB.